Bridging Knowledge and Action: An AI-Enabled Communication Model for Ecological Education - Munandar, Alan; Medina, Hillary Tasya; Choiron, Nabhan Fuad (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2026)
Students often understand ecological issues but fail to translate knowledge into action. Existing studies mainly position artificial intelligence (AI) as a content-delivery tool rather than a communication infrastructure linking message design to behavioral outcomes. This study proposes a six-layer AI-Enabled Communication Model for Ecological Education based on instructional communication theory and the Knowledge–Attitude–Behavior framework. Using a systematic literature review (SLR) and thematic synthesis, 20 studies published between 2016 and 2026 were analyzed. Findings show that AI supports ecological learning through personalized messaging, interactive simulations, conversational agents, and continuous feedback. However, lasting behavioral change requires supportive school culture, teacher-guided value formation, and ecological projects. The proposed model integrates message design, AI-supported communication, feedback, action reinforcement, value habituation, and ethical governance to promote sustainable ecological behavior.